The Role of Manager Behavior in Explaining The Financial Planning and Financial Innovation of Small and Medium Enterprises - Ismanto, Hadi; Pebruary, Silviana (Indonesian Journal of Business and Entrepreneurship, 2023)
The major weakness of SMEs is in financial management and marketing. These problems obstruct their growth and ability to plan and innovate their business. This study examines the influence of personality, financial culture, and competence on SMEs' innovation and financial planning. The sample was determined by proportional random sampling repose industry type, and 285 complete data were analyzed. Data were collected through a structured offline questionnaire. A quantitative analysis approach was followed using a structural equation model. The results show that financial planning is an effective mediator of personality, financial culture, and competencies toward financial innovation. Personality and financial culture do not directly affect financial innovation but indirectly affect financial planning. However, competence directly affects financial innovation and indirectly passes through financial planning. This paper argues that SMEs have the potential to overcome economic crises by focusing on how they manage finance innovation and considering determining factors of financial planning and innovation. Finally, this study contributes to the literature on SME financial behavior and factors such as personality, financial culture, and competencies that leads to the recommendation of SME owners/managers to innovate in accessing finance. Keywords: competencies, financial culture, financial innovation, financial planning, personality